2021
DOI: 10.2147/ott.s300834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the UK Myeloma Research Alliance Risk Profile in Chinese Patients with Newly Diagnosed Multiple Myeloma without Autologous Stem Cell Transplantation

Abstract: Purpose Recently, the British Myeloma Research Alliance put forward a Myeloma Risk Profile (MRP) for the first time to stratify the prognosis risk of non-transplanted patients with multiple myeloma. However, only limited studies have evaluated the applicability of this model in the Chinese population. This study aimed to estimate the prognostic value of MRP in newly diagnosed multiple myeloma patients without autologous stem cell transplantation in China. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…8 Several retrospective studies, including those with patients treated with bortezomibbased regimens, have reported the usefulness of the MRP. 9,10 However, caution must be taken in interpreting these results as patient backgrounds in the studies were more heterogeneous than those of JCOG1105 due to the retrospective nature of the studies.…”
Section: Prognostic Impact Of the Uk Myeloma Research Alliance Riskmentioning
confidence: 99%
“…8 Several retrospective studies, including those with patients treated with bortezomibbased regimens, have reported the usefulness of the MRP. 9,10 However, caution must be taken in interpreting these results as patient backgrounds in the studies were more heterogeneous than those of JCOG1105 due to the retrospective nature of the studies.…”
Section: Prognostic Impact Of the Uk Myeloma Research Alliance Riskmentioning
confidence: 99%